Pelaksanaan Strategi Pembelajaran INCLUDE Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Inklusi Sekolah Menengah Pertama Negeri 3 Teras Boyolali Tahun Pelajaran 2016/2017 - Rahmadani, Caturisa, Dr. Ari Anshori, M.Ag (2017)
Inclusive school is a school which receives all kinds of students necessary. This school provides a proper education but it is suited to ability and necessary of each student and teachers aids and supports in order to students get their success. Sekolah Menengah Pertama Negeri 3 Teras Boyolali is directed by the government as an inclusive school so it is a must to receive students with special necessaries. However, the students condition, Pendidikan Agama Islam teaching and learning should be succeded. The teacher uses effective and efficient strategy for a special necessary students class and other normal student class. The problem of this research is "how is the effectiveness and efficiency of INCLUDE strategy in Pendidikan Agama Islam subject in inclusive school of Sekolah Menengah Pertama Negeri 3 Teras Boyolali in 2016/2017. The aim of this research is to know the effectiveness and efficiency of INCLUDE strategy in Pendidikan Agama Islam study subject in inclusive school of Sekolah Menengah Pertama Negeri 3 Teras Boyolali in 2016/2017. The location of this research is in Sekolah Menengah Pertama Negeri 3 Teras Boyolali with the research object is the students in VIII grade which is included students with intelegent disturbtion special needed students. This research is a field research and qualitative research. The technique of collecting data used in this research are interview, observation, and documentation. The methode of analyzing data of this research is inductive methode.Based on the analyzing of the data it can econcluded that the teacher identified the classroom demand consists of wall area, lightning, and table position.The teacher took a note of superiorities and necessaries of studying from academic aspect, socio-emotional development and physic development. The teacher took some checks on the students successful of learning through academic aspect as the daily exams, assignments, mid term test, and last term test, athough through socio-emotional development as the attitudes in class. The teacher found there is a dismatch between special necessary students and normal students. The dismatch can be resolve through the acommodation and modification. Beside that, the teacher does a different teaching like five times worship journal assignment. The teacher evaluated the students studying development that can be seen from the score and students work.